Aslan y Ezcurra, Argentina
Sede administrativa sella Hoechst Argentina en San Isidro, 1989.
Keywords: ASLAN Y EZCURRA Y ASOCIADOS ARQUITECTOS; ASLAN, JOSÉ; EZCURRA, HÉCTOR; ARGENTINA; SAN ISIDRO; ARQUITECTURA CORPORATIVA; EDIFICIOS DE OFICINAS